2021
DOI: 10.1186/s12872-021-02012-7
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0004104 knockdown alleviates oxidized low-density lipoprotein-induced dysfunction in vascular endothelial cells through targeting miR-328-3p/TRIM14 axis in atherosclerosis

Abstract: Background Circular RNAs have shown important regulatory roles in cardiovascular diseases, containing atherosclerosis (AS). We intended to explore the role of circ_0004104 in AS using oxidized low-density lipoprotein (ox-LDL)-induced vascular endothelial cells and its associated mechanism. Methods Real-time quantitative polymerase chain reaction and Western blot assay were conducted to analyze RNA levels and protein levels, respectively. Cell viabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…Additionally, Huang et al reported that TRIM14 could promote the activation of endothelium by regulating NF-κB signaling pathway [ 44 ]. Zhang et al found that TRIM14 overexpression largely overturned the protective role of miR-328-3p in ox-LDL-triggered dysfunction in human umbilical vein endothelial cells [ 21 ]. Here, an upregulation of TRIM14 was observed in CAD patient and ox-LDL-exposed CMECs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, Huang et al reported that TRIM14 could promote the activation of endothelium by regulating NF-κB signaling pathway [ 44 ]. Zhang et al found that TRIM14 overexpression largely overturned the protective role of miR-328-3p in ox-LDL-triggered dysfunction in human umbilical vein endothelial cells [ 21 ]. Here, an upregulation of TRIM14 was observed in CAD patient and ox-LDL-exposed CMECs.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-186-5p was reported to play a critical role in cardiovascular diseases [ 20 ]. Moreover, a recent study indicated that tripartite motif containing 14 (TRIM14) was involved in the progression of atherosclerosis [ 21 ]. Coincidently, we first found that circ_ROBO2 and TRIM14 shared the complementary binding sites for miR-186-5p using bioinformatics tools, which prompted us to establish a circ_ROBO2/miR-186-5p/TRIM14 regulatory network.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, exosomes from platelets, vessel cells ( He et al, 2018 ; Bai et al, 2020b ), inflammatory adipocytes ( Wadey et al, 2019 ) and dendritic cells increased the level of inflammatory factors and recruited inflammatory cells and promoted their adhesion to the vessel wall, leading to a chronic inflammatory response process in AS. Multiple circRNAs (circ_0004104 ( Zhang et al, 2021a ), circular ANRIL ( Song et al, 2017 ), circTM7SF3 ( Wang and Bai, 2021 ), circUSP36 ( Miao et al, 2021 ) and so on) were upregulated in AS and demonstrated to induce vascular EC injury and oxidative stress and inflammation. Circ_GRN and Circ_CHFR were also upregulated in atherosclerotic serum and expedited the inflammation of human vascular muscle cells ( Zhuang et al, 2020 ; Li et al, 2021a ).…”
Section: Ev-circrnas In the Progression Of Asmentioning
confidence: 99%
“…In fact, knock-down of Circ_0004104 led to an increase in miR-328-3p levels, which further resulted in a reduction of ox-LDL. 95 miR-206 is acted on similarly by CircTM7SF3, another circulating RNA. As CircTM7SF3 levels are reduced, miR-206 levels increase, which results in a reduction of ox-LDL.…”
Section: Introductionmentioning
confidence: 99%